Components of visual perception in marketing contexts: a conceptual framework and review - Sample, Kevin L.; Hagtvedt, Henrik; Brasel, S. Adam (Journal of the Academy of Marketing Science, 2020)
Visual perception is essential to marketing practice and theory. Based on literature in marketing and related fields, this article develops a conceptual framework comprising five main components of visual perception: illuminance, shape, surface color, materiality, and location. Additionally, a systematic review of related visual perception research within marketing over the past five decades engenders takeaways of theoretical and practical importance, and an analysis of gaps in the literature reveals promising avenues for future research. The material presented includes coherent definitions, illustrative infographics, and accessible tables.